Dissection of the Antibody Response against Herpes Simplex Virus Glycoproteins in Naturally Infected Humans - Cairns, Tina M. (J Virol, 2014)
Relatively little is known about the extent of the polyclonal antibody (PAb) repertoire elicited by herpes simplex virus (HSV) glycoproteins during natural infection and how these antibodies affect virus neutralization. Here, we examined IgGs from 10 HSV-seropositive individuals originally classified as high or low virus shedders. All PAbs neutralized virus to various extents. We determined which HSV entry glycoproteins these PAbs were directed against: glycoproteins gB, gD, and gC were recognized by all sera, but fewer sera reacted against gH/gL. We previously characterized multiple mouse monoclonal antibodies (MAbs) and mapped those with high neutralizing activity to the crystal structures of gD, gB, and gH/gL. We used a biosensor competition assay to determine whether there were corresponding human antibodies to those epitopes. All 10 samples had neutralizing IgGs to gD epitopes, but there were variations in which epitopes were seen in individual samples. Surprisingly, only three samples contained neutralizing IgGs to gB epitopes. To further dissect the nature of these IgGs, we developed a method to select out gD- and gB-specific IgGs from four representative sera via affinity chromatography, allowing us to determine the contribution of antibodies against each glycoprotein to the overall neutralization capacity of the serum. In two cases, gD and gB accounted for all of the neutralizing activity against HSV-2, with a modest amount of HSV-1 neutralization directed against gC. In the other two samples, the dominant response was to gD. IMPORTANCE Antibodies targeting functional epitopes on HSV entry glycoproteins mediate HSV neutralization. Virus-neutralizing epitopes have been defined and characterized using murine monoclonal antibodies. However, it is largely unknown whether these same epitopes are targeted by the humoral response to HSV infection in humans. We have shown that during natural infection, virus-neutralizing antibodies are principally directed against gD, gB, and, to a lesser extent, gC. While several key HSV-neutralizing epitopes within gD and gB are commonly targeted by human serum IgG, others fail to induce consistent responses. These data are particularly relevant to the design of future HSV vaccines.